2023
DOI: 10.1002/adfm.202213675
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing High‐Nickel Cathodes with High‐Voltage Electrolytes

Abstract: Electrolytes connect the two electrodes in a lithium battery by providing Li + transport channels between them. Advanced electrolytes are being explored with high-nickel cathodes and the lithium-metal anode to meet the high energy density and cycle life goals, but the origin of the performance differences with different electrolytes is not fully understood. Here, the mechanisms involved in protecting the high-capacity, cobalt-free cathode LiNiO 2 with a model high-voltage electrolyte (HVE) are delineated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…Interestingly, component 2 shows a similar shape to the dQ dV −1 analysis of the charge curve, where each phase transition corresponds to a peak in the dQ dV −1 curve. [ 37 ] As Li + diffusion kinetics within LiNiO 2 cathode particles follows the same trend of the dQ dV −1 curve, [ 23 ] component 2 may represent the kinetic effect of LiNiO 2 during de‐lithiation, and the corresponding weight 2 represents the kinetic contribution to the overall charge capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, component 2 shows a similar shape to the dQ dV −1 analysis of the charge curve, where each phase transition corresponds to a peak in the dQ dV −1 curve. [ 37 ] As Li + diffusion kinetics within LiNiO 2 cathode particles follows the same trend of the dQ dV −1 curve, [ 23 ] component 2 may represent the kinetic effect of LiNiO 2 during de‐lithiation, and the corresponding weight 2 represents the kinetic contribution to the overall charge capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The lab-generated dataset was collected in CR-2032 type coin cells with LiNiO 2 as the cathode and Li metal as the anode. [21][22][23] The coin cells were tested at a C/10 rate three times after assembling, followed by cycling at room temperature with a C/2 charge rate and 1C discharge rate. The C/2 charge curves of these cells were used for this study, and a total of 10066 charge curves were selected with a minimum charge capacity of 160 mA h g −1 .…”
Section: Data Generationmentioning
confidence: 99%
“…Accordingly, different functional additives of electrolyte are in high demand for the construction of a stable cathode-electrolyte interface. [96][97][98][99] For example, Cheng et al 100 found that the addition of lithium diuoro(oxalato)borate and tris(trimethylsilyl)phosphate into the carbonate electrolyte contributed enormously to the microcrack suppression. During cycling, these two additives would undergo oxidization and decomposition to form stable F, B, and Si-rich cathode-electrolyte interface (CEI) layers, whose existence could act as effective protective layers to diminish the continuous decomposition of the electrolyte and the dissolution of transition metal ions.…”
Section: Surface Modicationmentioning
confidence: 99%
“…Each peak in the dQ dV −1 curve represents a two-phase coexistence region during cycling, and the notations of the two-phase coexistence are labeled in the figure. 24 Compared to cycle 1, the intensity of the H1-M phase transition decreases at cycle The loss of lithium inventory could be from the formation of side reaction products on the surface of both electrodes (i.e., SEI on the anode and cathode-electrolyte interphase (CEI) on the cathode) and the formation of inactive metallic Li 0 on the Cu substrate. 25 Electrolytes play a crucial role in the formation of SEI, CEI, and inactive metallic Li 0 , leading to different CE values.…”
mentioning
confidence: 99%
“…But interestingly, the three discharge curves almost overlap in the voltage range of 4.4–3.8 V before a sudden drop of the voltage at around 3.7 V. To uncover the degradation mechanisms, Figure S2 compares the incremental capacity analysis (d Q d V –1 ) of the cycling curves at cycles 1, 50, and 100. Each peak in the d Q d V –1 curve represents a two-phase coexistence region during cycling, and the notations of the two-phase coexistence are labeled in the figure . Compared to cycle 1, the intensity of the H1-M phase transition decreases at cycle 50, and the phase transition almost totally disappears at cycle 100.…”
mentioning
confidence: 99%